2008
DOI: 10.1111/j.1567-1364.2008.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquinone biosynthesis inSaccharomyces cerevisiae: the molecular organization ofO-methylase Coq3p depends on Abc1p/Coq8p

Abstract: Coenzyme Q is a redox-active lipid that functions as an electron carrier in the mitochondrial respiratory chain. Q-biosynthesis in Saccharomyces cerevisiae requires at least nine proteins (Coq1p-Coq9p). The molecular function of Coq8p is still unknown; however, lack of Q and the concomitant accumulation of the intermediate 3-hexaprenyl-4-hydroxybenzoic acid in the absence of Coq8p suggest an essential role in Q-biosynthesis. Localization studies identify Coq8p as a soluble mitochondrial protein, with character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 56 publications
9
102
0
1
Order By: Relevance
“…3A). Although previous studies indicated that the Coq3 polypeptide was labile in ⌬coq strains (6), subsequent experiments performed in the presence of both protease and phosphatase inhibitors preserved steady state levels of Coq3 (12,15). In agreement, Coq3 levels were unaffected in ⌬coq5 or ⌬coq6 cells (Fig.…”
Section: Overexpression Of Coq8 Restores Steady State Levels Of Coq Psupporting
confidence: 64%
See 2 more Smart Citations
“…3A). Although previous studies indicated that the Coq3 polypeptide was labile in ⌬coq strains (6), subsequent experiments performed in the presence of both protease and phosphatase inhibitors preserved steady state levels of Coq3 (12,15). In agreement, Coq3 levels were unaffected in ⌬coq5 or ⌬coq6 cells (Fig.…”
Section: Overexpression Of Coq8 Restores Steady State Levels Of Coq Psupporting
confidence: 64%
“…Coq8 has been proposed to possess a kinase activity (11) and has been shown to be necessary for the existence of phosphorylated forms of Coq3, Coq5, and Coq7 in vivo (12,15). A G130D mutation in Coq8 abolishes the phosphorylated form of Coq3 suggesting that this mutation impairs the kinase activity (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ding and colleagues (10) developed a statistical method for measuring the overlap between skin cells and lymphoblastoid cells in levels of gene expression and found that ϳ70% of the quantitative trait loci detected in lymphoblastoid cells were also observed in skin. Our findings are consistent with the idea that Q 10 content in cells reflects not only expression of Ն11 genes required for de novo synthesis, but also the assembly of a mitochondrial multisubunit protein-lipid complex known to be modulated by phosphorylation (54,56,64). Such multisubunit complexes may be particularly sensitive to polymorphisms.…”
Section: Discussionsupporting
confidence: 79%
“…The yeast Coq4 and Coq9 polypeptides co-purify with other Coq polypeptides and both migrate at high molecular mass in separation of digitonin extracts of mitochondria [18][19][20][21]. Thus, we used the Coq4 and Coq9 polypeptides as sensitive indicators of the state of the high molecular mass Coq complexes.…”
Section: The Coq4 and Coq9 Polypeptides Are Sensitive Indicators Of Tmentioning
confidence: 99%